Anti-inflammatory and antioxidant properties of Sargassum polycystum ethyl acetate extract from Indonesia - Erlia Anggrainy Sianipar; Shannen Ivanka Gunardi (Shahrekord University of Medical Sciences, 2023)
Introduction: Inflammatory diseases, including asthma, osteoarthritis, rheumatoid arthritis, and cancer persist with relatively high incidence, which highlights the need to explore natural alternatives such as the bioactive substances of brown algae (Sargassum polycystum). Certain substances, such as phenolics and flavonoids, have been demonstrated to have an association with antioxidant activity because of their capacity to fend off free radicals, which cause inflammation. The purpose of this study was to look into the inflammatory inhibition and antioxidant activity of an ethyl acetate extract of S. polycystum from Indonesia. Methods: After maceration in ethyl acetate (1:4 w/v) for 24 hours, the total phenolic and flavonoid content of S. polycystum extract was measured using the colorimetric method. The antioxidant activity was tested using 1,1-diphenyl-2-picrylhydrazyl (DPPH), and the models of paw edema induced by carrageenan were used to assess inflammatory inhibition activity. Results: The findings revealed that S. polycystum had a weak antioxidant with a half-maximal inhibitory concentration (IC50) value of 605.24 ± 26.53 g/mL. Furthermore, it had 23.509 ± 0.109 mg gallic acid equivalents/gram (GAE/g) and 15.186 ± 0.046 mg quercetin equivalents/ gram (QE/g) of total phenolic and flavonoid compounds, respectively. At 200, 400, and 800 mg/ kg BW doses, S. polycystum had inflammatory inhibition percentages of 53.80 ± 4.68%, 62.35 ± 4.05%, and 60.90 ± 2.88%, respectively. Conclusion: Sargassum polycystum ethyl acetate extract inhibited inflammation. However, further study is needed to examine the safety, identification, separation of the relevant substances involved, and the precise mechanism of action.